ARCHITECTURAL DESIGN OF THE AL-MUTTAQIN MOSQUE AT MTS AL-MUTTAQIN, PLEMAHAN, KEDIRI REGENCY, EAST JAVA, INDONESIA - Sumarwoto, Imam (Universitas PGRI Sumatera Barat, 2025)
The design of the MTs Al-Muttaqin Mosque in Plemahan, Kediri, East Java, is part of a community service project aimed at providing a positive contribution through the creation of a functional and aesthetic mosque. This study includes an analysis of community needs, environmental mapping, and the identification of relevant local characteristics. The methods used involve surveys, interviews, and literature studies to understand preferences and the need for worship spaces that support both spiritual and social activities. The findings highlight the importance of adequate prayer space, supporting facilities, accessibility, and the integration of local cultural values. The design was developed in collaboration with the local community and related stakeholders through active participation. This mosque is expected to serve as a center for religious and social activities and as a model for mosque design based on local community needs.